Pengembangan Model Edukasi Pelaksanaan Discharge Planning Berbasis Telenursing untuk Meningkatkan Self Care Management Ostomate - Etri Selpawani; Saldy Yusuf; Syahrul Syahrul; Elisa Sinaga (Journal of Telenursing (JOTING), 2023)
The purpose of this research is to develop an educational model for implementing discharge planning by utilizing telenursing through creating video content using the METHOD (Medication, Environment, Treatment, Health teaching, Outpatient referral, Diet) approach to improve ostomate self-care management. The research method used was the Delphi studi and this research was conducted in three phases, namely a literature review related to the content and educational model of discharge planning, video content development using the Delphi study accompanied by an evaluation of the validity of the video content by experts, and a pilot study to evaluate the ability of self care management ostomate using the Self Care Agency Scale (SCAS) questionnaire. The research result obtained 17 educational discharge planning items were obtained from the results of the literature review and the Delphi study which were used as video content. The results of the evaluation after the educational intervention showed that there was a significant increase in ostomate self-care management skills (p = 0.000). In conclusion, discharge planning education based on telenursing which is based on the METHOD approach, and provided in video form can be one of the recommendations for interventions in nursing practice to improve ostomate self care management. Keywords: Discharge Planning Education, Ostomate, Self Care Management